2015
DOI: 10.1021/cs501763k
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Oxidation Activity of Pt Nanoclusters via Encapsulation

Abstract: To tailor the catalytic activities of metal catalysts at will to achieve efficient conversion in chemical processes remains a challenge, particularly for noble metals, such as Pt. We demonstrate herein that encapsulation within the carbon nanotube (CNT) channels with a diameter of 1.0−1.5 nm not only allows restriction of the size of Pt nanoclusters around 1.0 nm but also enables modulating of the Pt species at the active reduced states through host−guest interaction. The encapsulated Pt is protected from oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 43 publications
(55 reference statements)
1
54
0
Order By: Relevance
“…66 The oxidation of benzyl alcohol to benzaldehyde can be catalysed by birnessite, a manganese dioxide mineral with intercalated potassium ions, and nanoparticles of this structure were encapsulated within MWCNT by Yang and co-workers. 72 The direct comparison of PtNP encapsulated within both CNT and a zeolite H-mordernite, possessing linear cavities of comparable diameter to CNT, shows that inorganic nanoscale hosts do not necessarily induce the same confinement effects (Fig. The oxidation of toluene catalysed by PtNP further emphasises the importance of the carbon nanotube host in achieving such results.…”
Section: Oxidationmentioning
confidence: 99%
“…66 The oxidation of benzyl alcohol to benzaldehyde can be catalysed by birnessite, a manganese dioxide mineral with intercalated potassium ions, and nanoparticles of this structure were encapsulated within MWCNT by Yang and co-workers. 72 The direct comparison of PtNP encapsulated within both CNT and a zeolite H-mordernite, possessing linear cavities of comparable diameter to CNT, shows that inorganic nanoscale hosts do not necessarily induce the same confinement effects (Fig. The oxidation of toluene catalysed by PtNP further emphasises the importance of the carbon nanotube host in achieving such results.…”
Section: Oxidationmentioning
confidence: 99%
“…Nanoclusters with a high volume/surface ratio and quantum effect have been proven to be efficient catalysts in various useful reactions. To date, several synthetic approaches have been developed to fabricate these small nanoparticles, including solution-phase reduction, gas-phase synthesis, and the ligand-assisted approach [25][26][27][28][29]. However, the fabrication of small nanoparticles is still challenging because of their severe aggregation, wide size distribution, low output, and low activity.…”
Section: Introductionmentioning
confidence: 99%
“…As clarified by recent theoretical studies [9], the external surface of CNT presents more electron density than the internal surface, which results in significant Researchers have systematically revealed that the confinement interaction of CNTs could influence the chemical properties of metal or metal oxides NPs (e,g., Fe 3 O 4 [10], Fe and Fe 2 O 3 [11], Ru [12], Re species [13] and Pt [14] ), especially associated with the tuning of redox/oxidation property through host-guest interaction. For example, Bao et al found that encapsulation interactions of CNT could not only reduce the size of Pt nanoparticles, but also prefer the Pt species at active reduced states [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bao et al found that encapsulation interactions of CNT could not only reduce the size of Pt nanoparticles, but also prefer the Pt species at active reduced states [14]. In addition, the metal NPs (i.e., Pd, Rh, Fe, Ru and so on) encapsulated inside the nanotube could deliver enhanced catalytic activity or higher enantioselectivity towards a wide range of reactions, such as oxygen reduction reaction (ORR) [15], Fisher-Tropsch synthesis (FTS) reaction [16][17][18] and liquid phase hydrogenation reaction [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation